PROBLEMS OF GREENING THE PROFESSIONAL TRAINING OF FUTURE BUILDERS (Innovative professional education, 2024)
The problems of ecologization of the professional training for future construction workers in educational institutions are considered. The essence of ecological education isrevealed and five main problems hindering its implementation are formulated. Possible ways of solving them are indicated. An example of a new educational and methodological support for environmental cases is given. The reveal the importance of ecologization for the sustainable development of the construction industry.
Keywords: ecologization of professional training, problems of ecologization, ecological cases, tiler-facer, painter